The Impact of Injury History on Anxiety and Motivation of West Java Student Athletes - Putri Fadilah Amelia Amelia; Mustika Fitri; Herman Subarjah; Hilmy Apriady; Mohammad Firdaus Ahmad (Journal of Sport Science and Fitness, 2026)
Background: Injuries are a risk in sports that affect athletes not only physically but also psychologically, such as through anxiety and motivation. The research problem is the lack of clarity regarding the impact of injury history on the psychological aspects of student athletes. Objectives: This study aims to determine the effect of injury history on anxiety and motivation among student athletes in West Java. Method: The study employed a quantitative approach using simple linear regression analysis on 42 athletes selected through purposive sampling. The instruments included an injury history questionnaire, the General Anxiety Disorder-7, and the Sport Motivation Scale. Result: The results showed that injury history did not have a significant effect on anxiety (Sig. = 0.219), but had a near-significant relationship with motivation (Sig. = 0.055), indicating a tendency toward increased motivation. Conclusion: The conclusion indicates that injury history does not significantly affect anxiety and only shows a tendency toward motivation; therefore, it cannot be concluded as a statistically significant relationship. These findings underscore the importance of an evidence-based holistic approach in athlete training and recovery.